On the Requirements Engineer Role. - FRANCH, XAVIER; PALOMARES, CRISTINA; GORSCHEK, TONY (Communications of the ACM, 2021)
The article discusses the importance of the role of requirements engineering (RE) and requirements engineers in computer software development and presents information from a study conducted by the authors that queried information technology (IT) professionals from several business enterprises. According to the study, organizations rely upon requirements engineers in all facets of projects, requirements engineers perform tasks outside of RE tasks, and larger firms define the RE role better than small companies.